MAKNA TRADISI MAMACAH DALAM PERSPEKTIF SOSIAL DAN KOMUNIKASI BUDAYA - Isyanto, Isyanto; Yuliastina, Roos; Suhartono, Suhartono (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This research examines the Madurese people who have local wisdom and cultural wealth in the form of oral literature, namely, the mamaca tradition. Nowadays, the development of the oral literary tradition in Madura is quite worrying, including the mamaca tradition. This tradition takes place in the midst of advanced technological advances which are one of the things that the millennial generation likes most. Thus, the mamacah tradition which should be a self-identity is increasingly being erased, left behind by the next generation. The approach used in this study is a qualitative research approach. Where qualitative research is research that produces descriptive data in the form of written or spoken words consisting of behaviors that can be observed by someone. While the method used in conducting this research is in the form of observation, recording, interviews, and recording. The findings in this study are in the form of the mamacah tradition carried out in Rubaru District, Sumenep Regency